A game-theoretic approach to an oligopolistic transportation market: Coopetition between incumbent systems subject to the entrance threat of an HSR service. (November 2022) - Rategh, Yalda; Tamannaei, Mohammad; Zarei, Hamid
Highlights: Competition and coopetition of airline, intercity bus, and entrant HSR operators. The main driver for the operators' pricing competition is identified. Non-pricing strategies may be necessary for the incumbent operators' survival. Short-term government policies may not guarantee the passengers' full satisfaction. Abstract: We investigate pricing competition between passenger transportation modes in a transportation market by using a game-theoretic approach. Airplane and intercity bus operators are considered as incumbent; while a High-Speed Rail (HSR) operator decides on whether or not to enter the market. If the incumbent operators evaluate the entrance threat of HSR as serious, they have two alternatives: a barrier pricing strategy (BPS) to deter its entrance, and an accommodation pricing strategy (APS). Their interaction involves two competitive and cooperative aspects, called the coopetition interaction. Moreover, we extend the analysis to a real-world situation in which a government, as a social welfare maximizer, intends to certify and support one operator out of two candidate HSR operators. Our analyses reveal that: (a) the passengers' heterogeneity (with respect to their perceptions on the operators' quality of services) is the main driver for pricing competition between the three operators. (b) Under certain conditions, implementing a BPS is not only precluded for the incumbent operators, but also their pricing strategies cannot even guarantee their survival in the market. To address this issue, we suggest the incumbent operators adopt non-pricing strategies. Nevertheless, an incumbent operator may freely ride on the other ones' non-pricing strategy. (c) Under a short-term (long-term) planning horizon, the government should specifically concentrate on compensating for the HSR operating cost (procurement cost of rolling stock). (d) In contrast to the short run, government expenses and the HSR's profit exploitation provide a strong foundation for the passengers' full satisfaction in the long run.